Measures taken for bovine tuberculosis prevention among butchers in two major abbatoirs in ibadan,south-western nigeria (2012)
Correct measures towards prevention are important in achieving global tuberculosis eradication. A study was conducted to determine the measures taken by butchers for bovine tuberculosis (BTB) prevention at Akinyele and Bodija Municipal Abattoirs in Ibadan, south-western Nigeria, with a view to providing vital information for BTB control. Four hundred and fifty butchers from the two abattoirs were randomly selected for this study and data were collected through the method of questionnaires and analysed using SPSS version 12.0. The response rate was 97.1% (437/450). Our findings revealed that their approach towards BTB prevention included practice of good hygiene (17.6%), hand washing (15.6%) after each day’s work, wearing protective materials like gloves and boots (14.4%), use of preventive medicine (14.2%), immunization (12.6%), prayer (10.1%), use of herbs (9.8%) and limited contact with animals or carcasses (5.7%). On limiting cattle to cattle spread of bovine tuberculosis, early isolation of infected animals (29.2%), avoidance of close contact with the infected animals (23.3%), prompt reporting to the veterinarians (22.2%), avoidance of overcrowding of cattle in the kraal (14.9%) and early notification by the cattle handlers (10.3%) were the practices highlighted. Age groups (p= 0.006), sex (p=0.019) and length of working experience (p=0.033) were significant factors associated with the butchers’ correct preventive measures against the spread of bovine tuberculosis. This study provides vital information for the stakeholders in the Public Health Sector for informed steps to be taken to better position the livestock workers especially butchers in the drive towards eradication of tuberculosis including BTB in Nigeria.